An exploratory and confirmatory composite analysis of a scale for measuring privacy concerns - Mwesiumo, Deodat; Halpern, Nigel; Budd, Thomas; Suau-Sanchez, Pere; Bråthen, Svein (Elsevier, 2021)
This paper reports a confirmatory composite analysis of a scale for measuring privacy concerns, and the effect of privacy concerns on the willingness to provide personal data. The analysis is based on 468 survey responses, divided into two contexts: airport digital services and online retail services. Results from both contexts confirm that privacy concerns consist of a third-order construct comprising two-second order constructs (interaction management and information management) and a first-order construct (awareness). The effect of privacy concerns on the willingness to provide personal data is higher in the airport digital context than in the online retail context. Also, the relevance of the three dimensions varies by context. Thus, researchers must carefully consider their research context and include items for the most relevant dimensions of privacy concerns in measurement models. Likewise, managers must prioritise dimensions of privacy concerns according to their business context.
Keywords: Privacy concerns scale; Confirmatory composite analysis; Partial least squares path modelling; Airport management; Online retail